Voisin’s Rational Grazing system for small ruminant feeding in Mediterranean areas - Donnola M.; Primi R.; Ronchi B. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Small ruminant grazing systems in Mediterranean areas are still linked to traditional practices based on continuous grazing, which, in certain cases, lead to a suboptimal exploitation of the herbage and to a reduced economic and ecosystem performance. In South America, for at least 40 years, many farmers have adopted intensive (controlled) rotational or Voisin’ s Grazing System (VRG), to maximize the production of aboveground plant biomass and to increase profitability. Using portable and/or permanent fencing and watering systems, VRG consists in applying a high instantaneous stocking density, rotating the animals among paddocks to manage pasture growth and consumption, according to the growth rate of plants, species composition, soil and climatic conditions. The total time that animals occupy a paddock must be very short to prevent the grazing of regrowth in the same residence time. This technique, recently applied by small ruminant farmers, makes it possible to: (i) regenerate degraded pastures and meadows in marginal areas, (ii) increase harvesting efficiency and productivity of lowland pastures, (iii) obtain a diet more stable and of higher quality for livestock, (iv) increase the stock of carbon in soils, and (v) enrich plant and animal biodiversity as a result of increased soil fertility. From the literature, we draw some examples of VRG application in ruminant production, considering the most recent research works and independent observation, with the aim of listing the benefits that have been verified in terms of productivity, mitigation of CO2 emissions and effects on the ecosystem, as well as the possibilities of adoption in the Mediterranean basin.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)